In Vitro Examination of Effects of Hyperprolactinemia and Hypoprolactinemia on Seminal Vesicle Contractions - Firdolas, Fatih; Ogras, Mehmet Sezai; Ozan, Tunc; Onur, Rahmi; Orhan, Irfan (Elsevier Science Inc, 2013)
OBJECTIVE To investigate the contractile characteristics of the seminal vesicles in rats, in which hyperprolactinemia and hypoprolactinemia was induced by prolactin and bromocriptine administration. MATERIALS AND METHODS A total of 24 Wistar albino rats were randomly divided into 3 groups: control group, hyperprolactinemia group, and hypoprolactinemia group. The rats in the control group were administered 0.1 mL saline subcutaneously for 21 days. The rats in group 2 received prolactin 51 mu g/kg subcutaneously for 21 days. The rats in the third group received intraperitoneal bromocriptine mesylate at a dose of 66 mu g/kg. All the rats were decapitated at 21 days. The seminal vesicles were removed using a microsurgical technique, and the tissue sections were prepared (0.5 x 0.2 cm). These sections were suspended in the organ bath. Subsequently, contractions were induced using 10 mu mol acetylcholine or 100 mmol potassium chloride. RESULTS The amplitude values induced by potassium chloride in the prolactin group were significantly greater than those in the bromocriptine group or control group. Similarly, the amplitude values induced by acetylcholine were also significantly greater in the prolactin group than in the other 2 groups. CONCLUSION Experimental hyperprolactinemia results in an increase in the smooth muscle contraction and tonus of the seminal vesicles. The alterations in the smooth muscle tonus in the seminal vesicles and genitourinary tract might be involved in the etiology of infertility occurring in hyperprolactinemia. UROLOGY 81: 557-561, 2013. (C) 2013 Elsevier Inc.
Keywords: Prolactin; Diagnosis; Responses; Erectile; Tissue; Model